Esensi Guru Menurut Pendidikan Nasional dan Pendidikan Islam - Arif Ali Muntaha; Ahmad Suyuti; Mukh. Nursikin (AS-SABIQUN, 2022)
The teacher is a figure who plays a role in transferring knowledge to his students, both general knowledge and religious knowledge to cause behavior that reflects good morals to students. As Muslims we can see the essence of teachers according to Islamic education, and as citizens we can also see the essence of teachers according to national education. Departing from these two views, the ideas that are written about the essence of teachers according to national education and Islamic education. This research is using library research with literacy study methods, data collected from sources of books, documents and scientific articles relevant to the discussion, namely a description of the essence of teachers according to national education and Islamic education. The results of this study are First, in national education the essence of the teacher is the person who provides teaching and education to students to form good, with graduate qualifications that must meet to become a teacher and teacher is considered a position. Second, the essence of the teacher according to Islamic education, Islam views the teacher as someone who has knowledge of a science and practices his knowledge by providing teaching and education to students as a sign of the usefulness of the knowledge they have, in Islam the teacher is devotion.